一种基于计算机视觉的面部视频判别中医气血系统 (2024)
本发明公开了一种基于计算机视觉的面部视频判别中医气血系统，该系统包括视频采集模块、视频预处理模块、特征提取模块、气血辨识模块和模型升级模块；视频采集模块采集受试者面部视频；视频预处理模块将视频裁剪为视频帧；特征提取模块基于Transformer构建气血特征提取模型，使用多头注意力机制、3D卷积等深度神经网络提取所述视频帧的气血特征；气血辨识模块获取最终辨识结果，并通过多任务学习提升模型表现；模型升级模块通过提高模型对难以分类样本的关注度，实现模型闭环优化。本发明以面部视频为采样媒介并采用计算机视觉和人工智能技术构建气血特征提取模型，基于模型提取的气血特征实现中医气血辨证及分类，极大减少了人为干预。 The invention discloses a face video traditional Chinese medicine qi and blood distinguishing system based on computer vision. The system comprises a video acquisition module, a video preprocessing module, a feature extraction module, a qi and blood identification module and a model upgrading module. The video acquisition module acquires a face video of a subject; the video preprocessing module cuts a video into video frames; the feature extraction module is used for constructing a qi and blood feature extraction model based on Transform, and extracting qi and blood features of the video frame by using deep neural networks such as a multi-head attention mechanism and 3D convolution; the qi and blood identificati